Indicators of speed and strength abilities of young fencers 12-13 years old - Olena Nesen; Viktoriia Klimenchenko (Pedagogy of Health)
Background and Study Aim. The health of a young athlete in the early stages of training is a mandatory element of the training process. This is a guarantee of the integrity of the process of training athletes for the next stage of preliminary basic training. The purpose of the study is to determine the indicators of speed and strength qualities of young fencers 12-13 years old at the stage of initial training.